The DNA binding site of HMG1 protein is composed of two similar segments (HMG boxes), both of which have counterparts in other eukaryotic regulatory proteins. - Bianchi, M E (1992)
The mammalian nuclear protein HMG1 contains two segments that show a high sequence similarity to each other. Each of the segments, produced separately from the rest of the protein in Escherichia coli, binds to DNA with high specificity: four-way junction DNA of various sequences is bound efficiently, but linear duplex DNA is not. Both isolated segments exists as dimers in solution, as shown by gel filtration and chemical crosslinking experiments. HMG1-like proteins are present in yeast and in protozoa: they consist of a single repetition of a motif extremely similar to the DNA binding segments of HMG1, suggesting that they too might form dimers with structural specificity in DNA binding. Sequences with recognizable similarity to either of the two DNA binding segments of HMG1, called HMG boxes, also occur in a few eukaryotic regulatory proteins. However, these proteins are reported to bind to specific sequences, suggesting that the HMG box of proteins distantly related to HMG1 might differ significantly from the HMG box of HMG1-like proteins.